MELIHAT TINDAK PIDANA PENYELUNDUPAN (SMUGGLING OF MIGRANTS) PMI NON PROSEDURAL SEBAGAI SUATU KEJAHATAN YANG BERSIFAT VICTIMLESS - Bakhtiar, Masdar; Hanuun, Khoirunnisa Dhiyaa (Jurnal Ilmiah Kajian Keimigrasian, 2024)
The warm case of news about PMI-NP, which has recently been carried out by many Indonesians, has become a complex problem. In media reports, many said that PMI-NPs who were thwarted by their attempts to cross were called "Victims" of trafficking or Trafficking in Persons. However, if you look again at the elements that exist in recent cases, it is actually a criminal act of Smuggling of Migrants, not trafficking. Therefore, this paper will look at the aspects and involvement of the "victim" Smuggling of Migrants from smuggled people. This paper uses literature review. The conclusion is that from the analysis of legal elements with the perspective of victimology, it can be stated that the phenomenon could be a criminal act that is victimless or victimless. Considering that the person to be smuggled called "Victim" has awareness and also the freedom to choose whether or not a crime of Smuggling of Migrants occurs. Which means that the use or mention of Illegal Migrants who are smuggled people is given a predicate or replaced with a clause "Victim" is not appropriate and inappropriate. It is important to review and review related to the enforcement or criminalization of the Smuggling of Migrants crime itself so that its enforcement is more targeted and can have a deterrent effect on PMI-NPs who knowingly and deliberately violate the law.